Pneumatic Sucker-Rod Machine for Dispersing Solid Mineral Fertilizers - V. A. Makarov; O. I. Zhuravleva; A. V. Shemyakin (Сельскохозяйственные машины и технологии, 2019)
In the world practice of introducing solid mineral fertilizers, almost 90 percents of the machines used are equipped fertilizer application is about 10 percents. It has been still confi rmed that their small width of application results in insuffi cient productivity, and in practice they are not used for introducing the main amount of fertilizers in pre-sowing soil preparation. (Research purpose) Designing a pneumatic sucker-rod machine providing for increased uniformity of fertilizer dispersing when introducing the main amount of fertilizers and further dressing vegetative plants. (Materials and methods) The authors obtained relationships allowing to determine rational constructive-and-kinematic parameters of a device for fertilizer metering and distributing through ejectors and dispersing surfaces using the laws and methods of classical mechanics and mathematics. Experimental studies were carried out using a developed and manufactured sample, and testing its operability in fi eld conditions using standard and specifi c techniques. It was determined that the quality of fertilizer dispersing with a pneumatic sucker-rod machine is mainly aff ected by the uniformity of their supply by reel-type units to the air stream and rods with holes, and the pattern of fertilizer distribution to ejectors depending on the distance between them. (Results and discussion) The authors have made patterns of fertilizer transportation and metering with reel-type sowing units and determined the method and pattern of distributing an air-mineral mixture through the rod channels. The authors obtained a mathematical description of the processes of mineral fertilizer application, taking into account the qualitative indicators of their uniform dispersion over the fi eld surface. It was noted that the uneven distribution of fertilizers when the rod length is appropriate corresponds to the design standards. (Conclusions) The authors have revealed that the rate of distribution unevenness of ammonium nitrate amounted to 8 percents. It has been found that even at the machinery designing stage it is possible to evaluate performance indicators in terms of unevenness depending on the metering quality and the distance between sowing ejectors.